2023
DOI: 10.1161/strokeaha.122.040830
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Exchange Saturation Transfer Magnetic Resonance Imaging for Longitudinal Assessment of Intracerebral Hemorrhage and Deferoxamine Treatment at 3T in a Mouse Model

Abstract: BACKGROUND: Noninvasive imaging of molecular alterations after intracerebral hemorrhage (ICH) could provide valuable information to guide and monitor treatments. Chemical exchange saturation transfer (CEST) magnetic resonance imaging has demonstrated promises in identifying proliferation, necrosis, and changes in cellularity in brain tumors. Here, we applied CEST magnetic resonance imaging to monitor molecular changes in hematoma without and with treatment noninvasively over 2 weeks at 3T using end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In previous studies, Sawaya et al, Wang et al and Ma et al observed that asymmetry-based APTw imaging showed markedly elevated contrast values in rat models and in patients with acute and subacute cerebral bleeding, which very likely corresponded to accumulations of deoxygenized hemoglobin and mHb [ 13 , 19 , 20 , 34 , 35 , 36 ]. Lai et al, on the other hand, observed significantly reduced contrast values in the subacute stage of cerebral hemorrhage in a preclinical study, using an apparent exchange-dependent relaxation compensated metric of the APT (APT AREX ) [ 21 ]. Contrary to these findings, to our knowledge, there are no available published results on the CEST contrast behaviors of Hs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, Sawaya et al, Wang et al and Ma et al observed that asymmetry-based APTw imaging showed markedly elevated contrast values in rat models and in patients with acute and subacute cerebral bleeding, which very likely corresponded to accumulations of deoxygenized hemoglobin and mHb [ 13 , 19 , 20 , 34 , 35 , 36 ]. Lai et al, on the other hand, observed significantly reduced contrast values in the subacute stage of cerebral hemorrhage in a preclinical study, using an apparent exchange-dependent relaxation compensated metric of the APT (APT AREX ) [ 21 ]. Contrary to these findings, to our knowledge, there are no available published results on the CEST contrast behaviors of Hs.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, mHb and Hs not only have a strong influential impact on T 1 and T 2 , but should also contribute to the APT and ssMT pool. However, whilst several groups have demonstrated that CEST imaging of the APT can differentiate between acute and subacute stages of intracranial hemorrhage [ 19 , 20 , 21 ], little is known about the influence of mHb and Hs on the clinical performance of APT and ssMT imaging in patients with glioma in the post-radiotherapy interval. Furthermore, CEST contrasts are heavily dependent on the metrics used for their reconstruction form the Z-spectrum [ 7 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical exchange saturation transfer (CEST) MRI is a molecular imaging approach that enables the visualization of physiological environment in tissues by harnessing exchangeable protons in biomolecules as contrast agents. [1][2][3][4] By detecting these protons in an increasing library of biomolecules, which includes glucose, [5][6][7][8][9] mobile proteins and peptides, 10,11 lactate, 12 creatine, [13][14][15] glycogen, 16 and other metabolites, with high sensitivity and specificity, CEST MRI has shown promising clinical applications in disease diagnosis and guided treatment for many neurological diseases, including Alzheimer's disease (AD), 8,17 multiple sclerosis, [18][19][20][21] stroke, [22][23][24] and cancer. [25][26][27][28] For example, it has been demonstrated as a unique approach to differentiate tumor recurrence from radiation necrosis using the amide proton of proteins and peptides in cancer, which cannot be easily identify by other neuroimaging technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, Chemical Exchange Saturation Transfer Technology (CEST) MRI techniques have attracted interest as a robust imaging approach for probing molecular imaging changes in vivo [ 14 , 15 , 16 , 17 , 18 ]. CEST is a new MRI approach based on the theory of magnetization transfer (MT) and chemical exchange.…”
Section: Introductionmentioning
confidence: 99%